'Even' After Access to Financial Services? Ricocheting Gender Equations - Shoba Arun; Samuel Annim; Thankom Gopinath Arun (Institute for the Study of Labor (IZA), 2016)
The paper focuses on women's financial behaviour in their use of higher order financial services in Ghana and South Africa, inviting a gendered and social analysis of deconstructing financial behaviour. Women in South Africa are more likely to use general financial products than in Ghana, though in general more men use advanced investment products. Race has an important effect in South Africa. Much of these gender differentials is related to differences in gendered behaviour, yet generalizations on how gender relates to risk aversion is not supported. Rather non-financial approaches may explain how social relations propel women's decision to prioritise the use of financial services as a result of ascribed gender and social roles. These findings contribute to the debates on the feminisation of finance, as women are increasingly interpellated as financial subjects, manifesting the gendered organisation of global financial structures that operate on gendered norms and behaviour.
Keywords: O16; O55; A14; B54; 330; gender; access to finance; risk; Ghana and South Africa